Analyzing energy deprivation for cooking in Argentina and Brazil - María Ibáñez-Martín; Yormy Eliana Melo; María Florencia Zabaloy (Revista Iberoamericana de Estudios de Desarrollo)
Lack of access to clean cooking is one dimension of energy poverty that has called the attention of many international organizations and policymakers, due to the relevance of cooking, as an energy service, in the satisfaction of essential needs. The present paper has two central objectives: it intends to characterize the population with energy deprivation for cooking and detect if their characteristics are coincident in Brazil and Argentina, and it analyses whether the selection of traditional fuels for cooking is related to the presence of other socioeconomic deprivations. To fulfill these objectives, an analysis of descriptive statistics is performed, and logistic models are estimated during the period 2004-2014. From the descriptive analysis, it is found that the socioeconomic characteristics of the population that presents energy deprivation in cooking are markedly different from those that are not deprived in this dimension. In turn, there is a strong dependence between the multidimensional deprivations and energy poverty in cooking.